2018
DOI: 10.1080/17461391.2018.1449895
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations to maintain immune health in athletes

Abstract: Numerous studies over the last 35 years report an increase in upper respiratory infection (URI) symptoms in athletes during periods of heavy training and competition. Challenges athletes face such as heavy exercise and life stress influence immune function via activation of the hypothalamic-pituitary-adrenal axis and the sympathetic nervous system and the resulting immunoregulatory hormones. Both innate and acquired immunity are often reported to decrease transiently in the hours after heavy exertion, typicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
13

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(126 citation statements)
references
References 84 publications
4
109
0
13
Order By: Relevance
“…Essentially, intense exercise of short duration is associated with much weaker stimulation of the immune system than the stimulation associated with long-term effort of high intensity [42,43]. Moreover, exercise of high and very high intensity increases the risk of upper respiratory tract infections in contrast to regular moderate intensity physical activity [36,42,44,45]. Our previous study showed that Th cells play an important role in regulation and modulation of the immune response to progressive effort until exhaustion performed on a mechanical treadmill [20,35].…”
Section: Th Cell Subset Alterationsmentioning
confidence: 99%
“…Essentially, intense exercise of short duration is associated with much weaker stimulation of the immune system than the stimulation associated with long-term effort of high intensity [42,43]. Moreover, exercise of high and very high intensity increases the risk of upper respiratory tract infections in contrast to regular moderate intensity physical activity [36,42,44,45]. Our previous study showed that Th cells play an important role in regulation and modulation of the immune response to progressive effort until exhaustion performed on a mechanical treadmill [20,35].…”
Section: Th Cell Subset Alterationsmentioning
confidence: 99%
“…Regarding individual athletes, the risk of developing Covid-19 can be reduced by regular sleep, eating a wellbalanced diet, and staying well hydrated, to maintain the capacity of the immune system [28]. A proper intake of fruit and vegetables (7-8 portions per day) is beneficial, since these foods contain polyphenols and flavonoids that support immune function [29].…”
Section: Recommendations For Sports Health During the Sars-cov-pandemicmentioning
confidence: 99%
“…Recent studies in animals [34] and in men [35] shown the e cacy of massage in boosting effects on T cell repertoire and in decrease noradrenergic innervation of lymphoid organs. Lifestyles intervention and psychological methods has also been proven to be effective in boost the immune system, for example meditation and methods to copying with life stressors [36,37]. Quite simple activities, such as breathing control can be helpful in reducing stress, boosting immune system [38,39].…”
Section: Sport and Upper Respiratory Tract Infectionsmentioning
confidence: 99%